Home of the teacher training students: the Primary School Teachers’ House in Kalocsa - Ács-Bíró, Adrienn (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Our research presents the boarding school of the Roman Catholic primary school teachers’ training institution in Kalocsa: the Primary School Teachers’ House (1897-1950). The pioneering initiative brought to life by the Roman Catholic Primary School Teachers’ Association of the Kalocsa area could be realized with the help of the church suggested in its name. With its more than 50 year long existence it played a decisive role not only in the life of the primary school training of Kalocsa, but nationally as well and it contributed to the shaping of the personality of the future primary school teachers. The institution received the students of the primary school teachers’ institution and of the grammar school as a kind of boarding school, where they got unifi ed moral, physical and religious education in cooperation with the school.